Effects of mental accounting on purchase decision processes: A systematic review and research agenda - Florian Skwara (Journal of Consumer Behaviour, 2023)
This paper aims to systematically analyze and synthesize the existing research published on mental accounting and purchase decision processes by conducting a systematic literature review. Specifically, the paper aims to answer the question: “What are the effects of mental accounting on purchase decision processes?” Therefore, it identified 110 papers which contribute to achieving the research objective and which were selected using the same data collection, data analysis, and quality standards. After reviewing the identified publications, the paper finds that the existing literature can be structured along four main themes impacting purchase decision-making processes: (1) source of funds, (2) intended use of funds, (3) pricing, and (4) payments. The paper shows that for each of the four themes there are multiple mental accounting effects with an impact on for example willingness to pay, the experienced pain of paying or the ultimate purchase decision. Further, the paper identifies potential directions for future research in mental accounting, including the influence of product categories on mental accounting, flexibility in budget setting and its impact on mental accounting behavior, long-term effects of mental budgeting on financial wealth, integration–segregation behavior in the context of pricing, the role of consumer characteristics on mental accounting behavior, and the impact of increased financial transparency through technology on mental accounting.
Keywords: 320